(untitled) (Baghdad Science Journal, 2013)
An experiment was conducted at botanical garden of Department of Biology ,College of Education (Ibn-AL –Haitham ,University of Baghdad during winter season of 2010 -2011.The aim of prsent study is to investigate the effect of Garlic (Allium sativum) extract and root extract of Ginger(Ziniber officinale)in two concentration of both extracts (20% and 30%)on growth and yield of (Cicer arietinum).The result showed that both extracts increased plant hight ,Chlorophyl content ,relative growth rate (RGR).Absolute growth rate (AGR),seeds yield .seed weight average ,biological yield ,carbohydrate and protein percentages in seeds,in comparsim with control plants .